Ritual Badudus, Kearifan Lokal dan Pendidikan Pernikahan Suku Banjar di Labuhanbatu - Nerisa Sertiawan; Nuriza Dora (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This research aims to ensure that future generations not only continue the tradition but also understand its meaning, thereby gaining knowledge and educational values while participating in it. The study employs a qualitative research approach with a descriptive-analytical method to explore the Badudus ritual from an educational perspective within the Banjar community of Tanjung Sarang Elang Village, Panai Hulu District, Labuhanbatu Regency. The findings reveal that the primary purpose of the Badudus ritual is to instill good character, morals, and ethics in the younger generation. This ritual serves not only as a traditional ceremony but also as a profound educational medium, integrating cultural values and Islamic teachings. The values imparted through the ritual include cleanliness and purity, solidarity and togetherness, spirituality and devotion to God, respect for customs and culture, as well as discipline and responsibility. However, the research also highlights challenges posed by modernization, urbanization, and shifting values among the younger generation, which may impact the ritual's future practice.